PENGARUH MEDIA PAPER TERHADAP HASIL BELAJAR MATEMATIKA MATERI PERKALIAN SISWA KELAS II SD - Jediut, Mariana; Purnama, Yuliana Sanita; Nardi, Mikael (Institut Daarul Qur'an Jakarta, Indonesia, 2023)
This paper is motivated by the lack of students' mathematics learning outcomes in multiplication material. One of the main reasons is the lack of use of learning media. This study aims to describe the effect of the multiplication board media on the mathematics learning outcomes of multiplication material for second grade students at SDK Beo Rahong. The type of research used is experimental research with a quantitative approach. The research design used is Quasi-Experimental Design. The data collection technique uses a description test technique. The population of this study was all students of SDK Beo Rahong, and the sample was second-grade students, totaling 35 people. Research data were analyzed by t-test. Based on the results of the t-test, obtained value of t count = 2.6298. If viewed from the dk value (18 + 17 – 2 = 33) at a significant level of 0.05, then the t table is 1.6924. Because t count > t table, the hypothesis states that there is an effect of the multiplication board media on the mathematics learning outcomes in multiplication material for second-grade students at SDK Beo Rahong is accepted. It can be seen from the average value after receiving treatment, where the average value of the experimental class = 84.71 while the control class = 78.06. Thus it can be concluded that there is a significant influence on the results of students' mathematics learning taught with the multiplication board.